WiFi-Friendly Building to Enable WiFi Signal Indoor - Suherman Suherman (Institute of Advanced Engineering and Science, 2018)
The 802.11 networks (wireless fidelity (WiFi) networks) have been the main wireless internet access infrastructure within houses and buildings. Besides access point placement, building architectures contribute to the WiFi signal spreading. Even dough WiFi installation in buildings becomes prevalent; the building architectures still do not take WiFi-friendliness into considerations. Current research on building and WiFi are on access point location, location based service and home automation. In fact, the more friendly the building to WiFi signal, the more efficient the 802.11 based wireless infrastructure. This paper introduces the term of WiFi-friendly building by considering signal propagations, the obstacle impact, as well as proposing an ornament-attaced reflector and a hole-in-the-wall structure to improve WiFi signal distribution. Experiment results show that obstacle materials made of concrete reducing WiFi signal the most, followed by metal and wood. Reflecting materials are able to improve the received signal level, for instance, the implemented ornament-attached reflector is able improving the received signal up to 6.56 dBm. Further, the hole-in-the-wall structure is successfully increasing WiFi signal up to 2.3 dBm.